The Development of Indonesian Horror Film Narratives “SI MANIS JEMBATAN ANCOL” in 1994 and 2019 - Agung Sandidi (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study explores the evolution of Indonesian horror film narratives by comparing Si Manis Jembatan Ancol (1994) and its 2019 remake. The 1994 version employs a lighter, entertainment-focused approach, emphasizing traditional supernatural elements with a straightforward storyline. In contrast, the 2019 film presents a complex narrative, incorporating social and psychological themes with nuanced characters. This transformation mirrors shifting audience preferences toward more emotional and realistic storytelling. The study also examines the impact of social, cultural, and technological factors on these narratives. The 1994 film reflects local traditions and beliefs, while the 2019 version integrates advanced CGI and contemporary social issues, influenced by global trends. Technological advancements in the remake enhance its visual and emotional depth, creating a more immersive horror experience. Ultimately, the study highlights how Indonesian horror films evolve in response to technological progress, cultural shifts, and the changing tastes of audiences over time.